The use of recovery strategies in professional soccer: a worldwide survey - Field, A.; Harper, L. D.; Chrismas, B. C. R.; Fowler, P. M.; McCall, A.; Paul, D. J.; Chamari, K.; Taylor, L. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To survey soccer practitioners` recovery strategy: (1) use, (2) perceived effectiveness, and (3) factors influencing their implementation in professional soccer.